1996
DOI: 10.1177/07399863960181005
|View full text |Cite
|
Sign up to set email alerts
|

Type A Personality, Job Satisfaction, and Tlrnover Intention among Certified Public Accountants: A Comparison of Euro-Americans and Hispanics

Abstract: Previous research has found accountants to possess the distinctive Type A personality, which may not be as prevalent in minority populations as it is in the Euro-American populations. This article reports on the results ofa survey of a sample of 860 Euro-American and 119 Hispanic certified public accountants. It assesses potential differences in personality, job satisfaction, and turnover intention by ethnicity, occupational setting, and level of decision-making authority. Analyses of the data found that ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The cause of low satisfaction is considered to be due to environmental factors. However, individual characteristics also play an important role in satisfaction within the same environment (Omundson, Schroeder, & Stevens, 1996). Omundson et al (1996) also found that “Type A Personality” has a significant positive relationship with job satisfaction.…”
Section: Intelligence Quotient Job Satisfaction and Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The cause of low satisfaction is considered to be due to environmental factors. However, individual characteristics also play an important role in satisfaction within the same environment (Omundson, Schroeder, & Stevens, 1996). Omundson et al (1996) also found that “Type A Personality” has a significant positive relationship with job satisfaction.…”
Section: Intelligence Quotient Job Satisfaction and Job Performancementioning
confidence: 99%
“…However, individual characteristics also play an important role in satisfaction within the same environment (Omundson, Schroeder, & Stevens, 1996). Omundson et al (1996) also found that “Type A Personality” has a significant positive relationship with job satisfaction. Gondal and Husain (2013) conducted comparative analysis between IQ scores and emotional perspective of intelligence for predicting achievements at the workplace.…”
Section: Intelligence Quotient Job Satisfaction and Job Performancementioning
confidence: 99%
“…In addition, it is the characteristic of the people involved in financial professions to often be reluctant to accept change in the working environment and to want tasks to remain at the same scheduled pace. One of the earlier empirical studies, which has investigated whether or not personality type may have an effect on one's choice of a college major or eventual career, indicated that some business professions such as accounting tend to be uncreative and unwilling to encounter "new ideas without being systematically prepared for a new change" and would prefer that everything remain constant (Omundson and Schroeder, 1996). Therefore, taking into consideration the characteristics of accountant and bureaucracy personality, the lack of communication efforts makes the transition process to accrual accounting more difficult in both developed and developing countries.…”
Section: Factors That Demonstrate Much Correlation With the Other Facmentioning
confidence: 99%
“…A possible explanation of why some individuals experience relatively high job satisfaction in a particular work environment while others experience relatively low job satisfaction in the same work environment is the difference in personality characteristics (Omundson, Schroder, &Stevens, 1996). In the same context, results of Schonfeld's (2001) study showed that support from nonwork sources was directly related to future improved symptom levels and self-esteem.…”
mentioning
confidence: 99%
“…Omundson et al (1996) assessed the potential differences in Type A personality, job satisfaction and turnover intention by ethnicity, occupational setting, and level of decision-making authority among two samples of Euro-American and Hispanic certified public accountants. Results showed that A personality was found to be significantly associated with occupational setting and level of decision-making authority.…”
mentioning
confidence: 99%